Antimicrobial Susceptibility Patterns of Pseudomonas Species Isolated from Various Clinical Samples at a Tertiary Care Hospital - Gyawali, Rabin; Khadka, Ram Bahadur; Shrestha, Basudha; Manandhar, Sarita (Journal of Institute of Science and Technology, 2020)
Considerable increase in the prevalence and multidrug-resistant (MDR) Pseudomonas has been observed with towering morbidity and mortality. As a consequence of the haphazard use of antimicrobials, the spread of antimicrobial resistance is now a global issue. This study aimed to access the distribution rate and antibiotic susceptibility patterns of Pseudomonas species isolated from various clinical specimens in Kathmandu Model Hospital, Nepal. During the study period, 1252 samples were collected, cultured and the organism was isolated and identified. The antimicrobial susceptibility testing was done using the modified Kirby-Bauer disc diffusion method as per CLSI guidelines. Out of 1252 samples, 28 clinical isolates of Pseudomonas species were isolated. The highest number of Pseudomonas spp. was isolated from swab samples that included pus, ear, and wound (46.4 %). Pseudomonas spp. demonstrated marked resistance against cefixime (96.4 %) and showed higher sensitivity to piperacillin/tazobactam (92.9 %). The result showed pus, wound exudates, ear discharges samples exhibit Pseudomonas as common etiology of infection. Pseudomonas spp. demonstrated highest sensitivity against piperacillin/tazobactam, amikacin, meropenem, gentamycin. The steady resistance of Pseudomonas spp. to most of the antibiotics, necessitates these drugs to be confined to extreme infections and hospital intensive care units to circumvent the speedy emergence of resistant strains.